The Cause of Drop of the Water Level of Underground Quaternary Aquifer of a Mine under Mining Influence. (20th June 2022) - Liu, Xianghong
Abstract : Water outburst on the coal mining face will result in the shutdown of the working face, tense mine connection, a sharp increase in mine drainage fee, and serious impact on normal production. In severe cases, it will give rise to mine flooding and endanger state property and life safety. Hydrogeochemical evolution characteristics of groundwater in different aquifers of the test mine were studied using the hydrogeochemical method, especially the source of chemical constituents of groundwater in different aquifers (type of water-rock interaction). Meanwhile, the GMS model was built, and change law of the stratigraphic texture of the gob overlying rock was studied based on site geological conditions. Specific to a sharp drop in Quaternary aquifer of the second west mining area of the test mine, the cause was analyzed based on site geological conditions and using hydrogeochemistry and geologic modeling method to ensure high yield and high efficiency of mine and provide references for production safety of mines of the same kind.